A Java Based Multimedia Distributed Collaborative Environment over the Internet - Chee, Boon Kok (1999)
Computer Supported Collaborative Work (CSCW) and distributed computing have been termed as the next paradigm of computing which allow users to interact and collaborate with each other seamlessly over the network. As a result, many collaborative distributed systems have been developed. Most of them have been implemented on proprietary systems instead of the Internet. Some may not provide necessary awareness for collaboration, while the rest still lack the real -world collaborative tools that are needed by the users. Therefore, there is a critical need for evaluating some of the proposed and existing systems to develop an effective collaborative distributed system that provides superior performance, simplicity and functionality. In this thesis, efforts have been focused on creating a Distributed Collaborative Environment (DCE) for efficient collaborative editing and interaction among the participating users. Firstly, the comparison and analysis of various existing collaborative systems are presented. Advantages and drawbacks of various systems are highlighted. Next, an alternative collaboration system has been developed which integrates most of the superior features of other systems while trying to avoid their drawbacks. The object-oriented design methodology is described together with the newly designed collaborative access protocol, SICAP. Finally, the implementation of the protocol on a client-server system is described. The resulting Java Distributed Collaborative Environment (JDCE) is a platform-independent collaborative system which has been developed using Java. It runs on the Internet and provides both asynchronous and synchronous collaboration. This environment has been built on top of an object-oriented layering architecture framework to achieve maximum extensibility and robustness. The system provides various services for state management, message routing and session control. No installations are required to access the system since the client application is built as a Java applet.